LFA-1 Mediates Cytotoxicity and Tissue Migration of Specific CD8+ T Cells after Heterologous Prime-Boost Vaccination against Trypanosoma cruzi Infection - Ferreira, Camila Pontes; Cariste, Leonardo Moro; Santos Virgílio, Fernando Dos; Moraschi, Barbara Ferri; Monteiro, Caroline Brandão; Vieira Machado, Alexandre M.; Gazzinelli, Ricardo Tostes; Bruna-Romero, Oscar; Menin Ruiz, Pedro Luiz; Ribeiro, Daniel Araki; Lannes-Vieira, Joseli; Lopes, Marcela de Freitas; et al. (Frontiers in Immunology, 2017)
Integrins mediate the lymphocyte migration into an infected tissue, and these cells are essential for controlling the multiplication of many intracellular parasites such as Trypanosoma cruzi, the causative agent of Chagas disease. Here, we explore LFA-1 and VLA-4 roles in the migration of specific CD8+ T cells generated by heterologous prime-boost immunization during experimental infection with T. cruzi. To this end, vaccinated mice were treated with monoclonal anti-LFA-1 and/or anti-VLA-4 in order to block these molecules. After anti-LFA-1, but not anti-VLA-4 treatment, all vaccinated mice displayed increased blood and tissue parasitemia, and quickly succumbed to infection. In addition, there was an accumulation of specific CD8+ T cells in the spleen and lymph nodes and a decrease in the number of those cells, especially in the heart, suggesting that LFA-1 is important for the output of specific CD8+ T cells from secondary lymphoid organs into infected organs such as the heart. The treatment did not alter CD8+ T cell effector functions such as the production of pro-inflammatory cytokines and granzyme B, and maintained the proliferative capacity after treatment. However, the specific CD8+ T cell direct cytotoxicity was impaired after LFA-1 blockade. Also, these cells expressed higher levels of Fas/CD95 on the surface, suggesting that they are susceptible to programmed cell death by the extrinsic pathway. We conclude that LFA-1 plays an important role in the migration of specific CD8+ T cells and in the direct cytotoxicity of these cells.